2022
DOI: 10.7759/cureus.25509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Morphogenetic Protein-2 (BMP-2)/Hydroxyapatite/In Situ-Formed Hyaluronan Hydrogel Composites on Bone Formation in a Murine Model of Posterolateral Lumbar Fusion

Abstract: Several types of calcium phosphate (CaP) biomaterial carriers have been designed to deliver bone morphogenetic protein-2 (BMP-2) to augment spinal fusion in spinal surgery. Here, we evaluated an in situ-formed hydrogel (IFH) constructed from hyaluronan (IFH-HA) combined with a BMP2/hydroxyapatite (HAP) composite in bone formation in a murine model of posterolateral lumbar fusion (PLF). HAP was submerged in HA-tyramine (TA) polymer solution containing horseradish peroxidase (HRP) and 2 µg BMP-2 (BMP2/HA-TA/HRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Generally, rodents exhibit rapid bone healing. Therefore, to evaluate differences in the effects of implant modifications, study periods of 4 weeks or less are typically used [54][55][56][57][58] Irish et al 59 assayed 4-, 8-, or 12-week follow-up times after implantation. They showed that implant placement significantly increased the mineralizing surface, mineral apposition rate, and bone formation rate in rats at the trabecular and endocortical surfaces mainly at 4 weeks.…”
Section: Protein Synthesesmentioning
confidence: 99%
“…Generally, rodents exhibit rapid bone healing. Therefore, to evaluate differences in the effects of implant modifications, study periods of 4 weeks or less are typically used [54][55][56][57][58] Irish et al 59 assayed 4-, 8-, or 12-week follow-up times after implantation. They showed that implant placement significantly increased the mineralizing surface, mineral apposition rate, and bone formation rate in rats at the trabecular and endocortical surfaces mainly at 4 weeks.…”
Section: Protein Synthesesmentioning
confidence: 99%